Pain perception and cardiovascular system response among athletes playing contact sports - Leznicka, K.; Pawlak, M.; Bialecka, M.; Safranow, K.; Cieszczyk, P. (Research in Sports Medicine, 2017)
The aim of this study was to determine whether the contact sports change the perception of pain as assessed by the cold pressor test (CPT), and if the test induces the same reaction of the cardiovascular system in contact athletes and non-athletes. The study involved 321 healthy men; 140 contact athletes and 181 students of the University of Szczecin (control). Pain threshold and pain tolerance were evaluated using CPT. Cardiovascular measurements were made during CPT. The contact athletes showed a much higher tolerance to pain than the control group (median time 120 vs. 94 s, respectively, p = 0.0002). The thresholds of pain in both groups did not differ significantly between the groups. Systolic blood pressure measured before and during the test in all three measurements was statistically significantly higher in athletes compared with the control group. Heart rate and diastolic blood pressure did not differ significantly between the studied groups.